Pengembangan Media Pembelajaran Sistem Penerangan Sepeda Motor Berbasis Android untuk Meningkatkan Hasil Belajar Siswa Kelas XI di SMK Negeri 3 Kabupaten Tangerang - Naufal Gesang Raharjo; Ranu Iskandar; Rizqi Fitri Naryanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The use of mobile devices in learning activities is becoming increasingly popular, especially with the presence of Android-based learning media. This study aims to develop Android-based learning media for motorcycle lighting system material, in order to improve the learning outcomes of class XI students at SMK Negeri 3 Tangerang Regency. The development was carried out using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The resulting application was validated by three experts with results ranging from "feasible" to "very feasible", and tested on students in small groups to see student responses and large groups to see the feasibility and effectiveness of the media. The test results showed very positive student responses (94.40%) and a significant increase in learning outcomes, with an average N-Gain of 0.71 or 71.64% in the "quite effective" category. This media is equipped with simulation features, interactive evaluations, and attractive and easy-to-use designs. This study concludes that Android-based learning media is not only feasible to use in the learning process, but is also able to increase student motivation and understanding in a more enjoyable and contextual way.